A modification of the CABARET scheme for the computation of multicomponent gaseous flows - Danilin, A.V.; Solovjev, A.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2015)
An explicit numerical algorithm for computing one-dimensional motion of multicomponent gaseous mixtures is proposed. A physical model and the equations of motion are presented in conservative and characteristic forms. The discretization of the governing equations is made in accordance with the CABARET (Compact Accurately Boundary Adjusting-REsolution Technique) approach. The proposed algorithm is tested on the Riemann problem with different gases on the different sides of the initial discontinuity. The resulting numerical solutions are compared with the analytical one and with those obtained by other numerical approaches. It is shown that the proposed algorithm is of high accuracy on the class of problems being considered.